How vocabulary is learned - Paul Nation (Universitas Katolik Indonesia Atma Jaya, 2017)
Vocabulary learning requires two basic conditions – repetition (quantity of meetings with words) and good quality mental processing of the meetings. Other factors also affect vocabulary learning. For example, learners may differ greatly in their motivation to engage in learning, and words may differ greatly in their learning burden. However, without quantity and quality of processing, learning cannot occur. The greater the number of repetitions, the more likely learning is to occur. The deeper and more thoughtful the quality of processing, the more likely learning is to occur. This paper explains quantity and quality, and shows how teachers and learners can increase the quantity and quality of their processing of vocabulary, thus increasing their vocabulary size.